2013
DOI: 10.1139/apnm-2012-0306
|View full text |Cite
|
Sign up to set email alerts
|

The ingestion of protein with a maltodextrin and fructose beverage on substrate utilisation and exercise performance

Abstract: The study investigated the ingestion of maltodextrin, fructose, and protein on exogenous carbohydrate oxidation (CHOEXO) and exercise performance. Seven trained cyclists and (or) triathletes (maximal oxygen consumption, 59.20 ± 9.00 mL · kg(-1) · min(-1)) performed 3 exercise trials that consisted of 150 min of cycling at 50% maximal power output (160 ± 11 W), followed by a 60-km time trial. One of 3 beverages were randomly assigned during each trial and consumed at 15-min intervals: (i) 0.84 g · min(-1) malto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Three additional studies found performance improvements as large as 7-8% for TT completion with glucose-fructose feedings relative to glucose-only feedings (11,50,63). Multiple transportable carbohydrates reduced GI complaints in several studies, including stomach fullness (31,39,50), nausea (40,50,62), abdominal cramps (40,53,62), and the urge to defecate (50). Two studies support the notion that fluid delivery is more rapid with glucose-fructose mixtures (30,50), whereas another suggests that decreases in plasma volume may be minimized (55).…”
Section: Multiple Transportable Carbohydratesmentioning
confidence: 92%
See 4 more Smart Citations
“…Three additional studies found performance improvements as large as 7-8% for TT completion with glucose-fructose feedings relative to glucose-only feedings (11,50,63). Multiple transportable carbohydrates reduced GI complaints in several studies, including stomach fullness (31,39,50), nausea (40,50,62), abdominal cramps (40,53,62), and the urge to defecate (50). Two studies support the notion that fluid delivery is more rapid with glucose-fructose mixtures (30,50), whereas another suggests that decreases in plasma volume may be minimized (55).…”
Section: Multiple Transportable Carbohydratesmentioning
confidence: 92%
“…In terms of performance, MTC improved outcomes (e.g., completion time, exercise capacity, and power output) in 8 studies (3,11,39,40,53,59,62,63). The largest effect on performance was from the study by Stannard et al (59), in which 1.0 g$min 21 of galactose led to ;15% slower time trial (TT) completion compared with glucose-galactose and glucosefructose mixtures.…”
Section: Multiple Transportable Carbohydratesmentioning
confidence: 99%
See 3 more Smart Citations